TRIM21 Aggravates Herpes Simplex Virus Epithelial Keratitis by Attenuating STING-IRF3-Mediated Type I Interferon Signaling - Tan, Tianchang; Xia, Likun (Frontiers in Microbiology, 2020)
Herpes simplex virus-1 (HSV-1) is the leading cause of infectious blindness in the developed world. HSV-1 infection can occur anywhere in the eye, and the most common presentation is epithelial keratitis. In the HSV epithelial keratitis mice model, we detected the expression of TRIM21 and then investigated the clinical relationship between TRIM21 and HSV epithelial keratitis by silencing TRIM21. Through the clinical scores and histopathology examination, we found that TRIM21 can effectively reduce the severity of HSV epithelial keratitis. Furthermore, silencing TRIM21 significantly controlled the virus particle release at 1, 3, and 5 days post-HSV-1 infection. Notably, the production of IFN-βwas enhanced, and the secretion of pro-inflammatory cytokines (IL-6 and TNF-a) was inhibited. Next, human corneal epithelial cells were pretreated with lentivirus or siRNA, respectively, so that TRIM21 expression was overexpressed or silenced. We focused on the regulation of STING-IRF3 and type I interferon signaling after infected with HSV-1. In conclusion, our results have identified that TRIM21 is abnormally high expressed in HSV epithelial keratitis. TRIM21 enhances the replication of HSV-1 in corneal epithelial cells via suppressing the production of type I IFN by inhibiting STING/IRF3 signaling. It also promotes the secretion of IL-6 and TNF-a, thereby aggravating the severity of HSV epithelial keratitis.